Learning Styles and Motivations of Individuals Without Prior Exposure to Augmentative and Alternative Communication. Issue 1 (January 2019) - Thiessen, Amber; Beukelman, David
Abstract : Purpose: Study purposes were to (a) examine achievement goal tendencies and learning mode preferences of adults who were unfamiliar with augmentative and alternative communication (AAC) facilitation, and (b) determine whether age and gender have an effect on these variables. Recruitment of untrained individuals allowed the researchers to simulate the experiences of individuals in the early stages of AAC facilitation. Method: Forty-one adults who were untrained in AAC facilitation completed surveys examining (a) achievement goal tendencies across 3 domains: mastery, performance, and social, and (b) learning mode preference across 4 domains: independent, small group, case study, and step-by-step. Participants were divided into groups on the basis of age (i.e., 26–40 years and 45–65 years) and gender (i.e., 16 males, 25 females). Results: Results indicate that participants were motivated to learn for mastery rather than social and performance purposes. In addition, they indicated a preference for learning through case studies. Younger adults rated performance and social learning higher than older adults. Also, women preferred small group instruction. Discussion/Conclusions: Facilitators play a vital role in successful AAC intervention, yet they often lack instruction to effectively fulfill this role. Clinicians should consider age and gender when designing instruction programs for these individuals.